Leadership, Teacher Empowerment, and Change Management: Fostering Transformational Practices in ‘Sekolah Penggerak’ Initiatives - Agus Subagio; Usman Radiana; Luhur Wicaksono (South Sulawesi Education Development (SSED), 2024)
The purpose of this article is to explore the intersection of leadership, teacher empowerment, and change management within the framework of the